2020
DOI: 10.1093/cid/ciaa578
|View full text |Cite
|
Sign up to set email alerts
|

Case Fatality Risk of the First Pandemic Wave of Coronavirus Disease 2019 (COVID-19) in China

Abstract: Objective To assess the case fatality risk (CFR) of COVID-19 in mainland China, stratified by region and clinical category, and estimate key time-to-event intervals. Methods We collected individual information and aggregated data on COVID-19 cases from publicly available official sources from December 29, 2019 to April 17, 2020. We accounted for right-censoring to estimate the CFR and explored the risk factors for mortality. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 28 publications
2
46
3
1
Order By: Relevance
“…Our estimates were also lower than those in Canada and the United States [ 25 ]. Compared with the CFR observed that ranged between 7% and 12% in the original epicentre of the pandemic, Wuhan [ 26 , 27 ], our estimates were lower although the CFR in Wuhan could be substantially lower if the clinically unobserved cases were taken into account [ 28 ]. Nevertheless, we acknowledged that CFR could vary by population composition (e.g.…”
Section: Discussioncontrasting
confidence: 61%
“…Our estimates were also lower than those in Canada and the United States [ 25 ]. Compared with the CFR observed that ranged between 7% and 12% in the original epicentre of the pandemic, Wuhan [ 26 , 27 ], our estimates were lower although the CFR in Wuhan could be substantially lower if the clinically unobserved cases were taken into account [ 28 ]. Nevertheless, we acknowledged that CFR could vary by population composition (e.g.…”
Section: Discussioncontrasting
confidence: 61%
“…Consecutive patients with multiple myeloma and related precursor diseases with confirmed presence of SARS-CoV-2 between March 1, and April 30, 2020, from five large academic centers in New York City were included in this study. In the general population, the probability of dying from COVID-19 has been reported to be between 1% and 6% including all COVID-19–positive cases, and between 6% and 26% for patients hospitalized due to the virus ( 1 3 18 19 20 ). Here, we show that among 75 patients with multiple myeloma admitted due to COVID-19, the mortality rate was 29%, which is thought to be on the high end of what has been reported in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In December 2019, international awareness emerged of a new coronavirus that had been rapidly spreading through the Chinese city of Wuhan. 1 By late February 2020, it became clear that severe outbreaks of SARS-COV-2, as the virus had been named, had resulted in almost 3000 deaths in Italy. 2 By March 2020 the virus had spread to many other countries in Europe and much further globally, with over 10,000 new cases per day.…”
Section: Introductionmentioning
confidence: 99%